Strategies to optimize concurrent training of strength and aerobic fitness for rowing and canoeing - Garcia-Pallares, J.; Izquierdo, M. (Sports Medicine, 2011)
During the last several decades many researchers have reported an interference effect on muscle strength development when strength and endurance were trained concurrently. The majority of these studies found that the magnitude of increase in maximum strength was higher in the group that performed only strength training compared with the concurrent training group, commonly referred to as the 'interference phenomenon'. Currently, concurrent strength and endurance training has become essential to optimizing athletic performance in middle- and long-distance events. Rowing and canoeing, especially in the case of Olympic events, with exercise efforts between 30 seconds and 8 minutes, require high amounts of maximal aerobic and anaerobic capacities as well as high levels of maximum strength and muscle power. Thus, strength training, in events such as rowing and canoeing, is integrated into the training plan. However, several studies indicate that the degree of interference is affected by the training protocols and there may be ways in which the interference effect can be minimized or avoided. Therefore, the aim of this review is to recommend strategies, based on research, to avoid or minimize any interference effect when training to optimize performance in endurance sports such as rowing and canoeing.